Design a better business : new tools, skills and mindset for strategy and innovation - Pijl, Patrick van der; Lokitz, Justin; Solomon, Lisa Kay (Hoboken, New Jersey : Wiley, 2016)
How to use this book: 8 Chapters; 48 Case studies; 20 Tools; 7 Core skills;Designers; 36 Hacks; >150 Visuals
1. Introduction: design a better business and the double loop -- 2. Prepare: prepare your team, your environment, and how you work -- 3. Point of view: be a rebel, develop your vision, create design criteria -- 4. Understand: understand your customer, context, and business -- 5. Ideate : learn to ideate, expand -- 6. Prototype :Bring ideas to life, sketch, and make prototypes -- 7. Validate: Find the riskest assumption, experiment, and pivot -- 8. When and how to scale, Investment Readiness Level
Includes index
Keywords: Business planning; Success in business